Vaccine Adjuvants: Mode of Action - Ulmer, Jeffrey (Frontiers in Immunology, 2013)
Vaccines were first introduced more than 200 years ago and have since played a key role in the reduction of morbidity and mortality caused by infectious diseases. Many of the safest and most effective vaccines in use today are based on attenuated live viruses, as they mimic a live infection without causing disease. However, it is not always practical to take this approach, such as when it may not be safe to do so (e.g., for viruses that cause chronic infections such as HIV) or may not be feasible to manufacture (e.g., for viruses that do not grow well in cell culture such as HCV). In addition, it may preferable in some cases to target immune responses toward specific antigens from the pathogen, rather than the entirety of the genome. In these cases, subunit vaccines consisting of antigens purified from the pathogen or produced by recombinant DNA technology are being developed. However, highly purified proteins are typically not inherently immunogenic, as they usually lack the means to directly stimulate the innate immune system, and often require the addition of adjuvants to enhance vaccine potency. Despite more than a century of human use, only a few adjuvants are licensed today. However many adjuvants have been tested in humans and are in advanced stages of development. Much of the early work on adjuvants discovery and development was empirical producing safe and effective products, but without a clear understanding of how they worked. Recent insight into the functioning of the innate immune system has demonstrated its important role in triggering and shaping the adaptive immune response to vaccines.